An introduction to game theory - Osborne, Martin J. (New York Oxford University Press, 2004)
An exposition of modern game theory suitable for advanced undergraduates, this book emphasizes the ideas behind the theory rather than their mathematical expression. It covers strategic, extensive, and coalitional games, and includes the topics of repeated games, bargaining theory, and evolutionary equilibrium.
Nash equilibrium : theory -- Nash equilibrium : illustrations -- Mixed strategy equilibrium -- Extensive games with perfect information : theory -- Extensive games with perfect information : illustrations -- Extensive games with perfect information : extensions and discussion -- Coalitional games and the core -- Bayesian games -- Extensive games with imperfect information -- Strictly Competitive games and maxminimization -- Rationalizability -- Evolutionary equilibrium -- Repeated games : The prisoner's dilemma -- Repeated games : general results -- Bargaining.
Keywords: Game theory